2009
DOI: 10.1289/ehp.0900696
|View full text |Cite
|
Sign up to set email alerts
|

Mass Lead Intoxication from Informal Used Lead-Acid Battery Recycling in Dakar, Senegal

Abstract: Background and objectivesBetween November 2007 and March 2008, 18 children died from a rapidly progressive central nervous system disease of unexplained origin in a community involved in the recycling of used lead-acid batteries (ULAB) in the suburbs of Dakar, Senegal. We investigated the cause of these deaths.MethodsBecause autopsies were not possible, the investigation centered on clinical and laboratory assessments performed on 32 siblings of deceased children and 23 mothers and on 18 children and 8 adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(115 citation statements)
references
References 18 publications
2
107
1
5
Order By: Relevance
“…Previous studies conducted around battery-related factories mostly focused on Pb pollution in the surroundings Onianwa and Fakayode, 2000), lead exposure of occupational workers (Ahmed et al, 2008;Chuang et al, 2008) or children Haefliger et al, 2009;Kaul et al, 1999;Kuijp et al, 2013) living in the vicinities of the plants. However, the exposure and combined health risks from other heavy metal(loid)s such as As, Cd, and Cr were rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted around battery-related factories mostly focused on Pb pollution in the surroundings Onianwa and Fakayode, 2000), lead exposure of occupational workers (Ahmed et al, 2008;Chuang et al, 2008) or children Haefliger et al, 2009;Kaul et al, 1999;Kuijp et al, 2013) living in the vicinities of the plants. However, the exposure and combined health risks from other heavy metal(loid)s such as As, Cd, and Cr were rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation in Nigeria revealed over 100 child fatalities related to lead poisoning (Dooyema et al 2011;Lo et al 2012). There are also reports of lead-related fatalities from Senegal (Haefliger et al 2009), where the World Health Organization (WHO) confirmed at least 18 children died from lead poisoning. Additionally, there are many reports of extremely elevated blood lead levels from other countries (Nduka et al 2008;Orisakwe and Nduka 2009;Shi et al 2009;Brown et al 2010;Niu 2010;Norman et al 2010;Ramos et al 2010;Rowley 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The burning of the e-waste is not a good option as either exposure to lead fumes or dust is known to cause multiple disorders, including neurological, cardiovascular and gastrointestinal diseases [20], exposure to cadmium fumes or dust leads to malfunctioning of the kidneys [21] and the respiratory system [22], and possibly lung cancer [23]. Either inhaled or swallowed through the food chain, the metals are capable of eliciting the same results as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%